PREVENTIVE AND CURATIVE EFFECT OF ETHYL ACETATE FRACTION OF GEODORUM LAXIFLORUM EXTRACT ON PARACTEMMOL (PCM)- INDUCED HEPATOTOXICITY IN RATS. - RAM CHANDRA BESRA,; LAKHAN MAJHEE,; JANARDAN SHARMA, (International Journal of Pharma and Bio Sciences, 2014)
Polyphenolic of medicinal plants and nutraceuticals are well known for the antioxidant property. In pathogenic conditions, antioxidants are being used to curtail the deleterious effect of free radicals globally. Geodorum laxiflorum has been used as folklore medicine in India for liver diseases. Therefore, the aim of this study was to investigate the preventive and curative activity of ethyl acetate fraction; compare the effect of fraction given by oral and intraperitoneal route of Geodorum laxiflorum methanolic extract in Paracetamol- induced liver damage rats. Study was conducted in Paracetamol-induced hepatoxicity model. Results of ethyl acetate fraction indicate that intraperitoneal route of administration was more effective than the oral route in both preventive and curative study. The study not only supports the traditional use but also provides the basis to identify, isolate molecule and develop a formulation from ethyl acetate fraction of the plant Geodorum laxiflorum.